Alteration of Colonic Mucin Composition and Cytokine Expression in Acute Swine Dysentery. Issue 3 (May 2021) - Lin, Susanne Je-Han; Arruda, Bailey; Burrough, Eric
Swine dysentery (SD) is an enteric disease associated with strongly β-hemolytic Brachyspira spp. that cause mucohemorrhagic diarrhea primarily in grower-finisher pigs. We characterized alteration of colonic mucin composition and local cytokine expression in the colon of pigs with acute SD after B. hyodysenteriae (Bhyo) infection and fed either a diet containing 30% distillers dried grains with solubles (DDGS) or a control diet. Colonic tissue samples from 9 noninoculated pigs (Control, N = 4; DDGS, N = 5) and 10 inoculated pigs experiencing acute SD (Bhyo, N = 4; Bhyo-DDGS, N = 6) were evaluated. At the apex of the spiral colon, histochemical staining with high-iron diamine–Alcian blue revealed increased sialomucin ( P = .008) and decreased sulfomucin ( P = .027) in Bhyo pigs relative to controls, with a dietary effect for sulfomucin. Noninoculated pigs fed DDGS had greater expression of sulfomucin ( P = .002) compared to pigs fed the control diet. Immunohistochemically, there was de novo expression of mucin 5AC (MUC5AC) in the Bhyo group while mucin 2 (MUC2) expression was not significantly different between groups. RNA in situ hybridization to detect the pro-inflammatory cytokine IL-1β often showed increased expression in the Bhyo group although without statistical significance, and this was not correlated with MUC5AC or MUC2 expression, suggesting IL-1β is not a major regulator of their secretion in acute SD. Expression of the anti-inflammatory cytokine TGF-β1 was significantly suppressed in the Bhyo group compared to controls ( P = .005). This study reveals mucin and cytokine alterations in the colon of pigs with experimentally induced SD and related dietary effects of DDGS.